Trading Dollars for Dollars: The Price of Attention Online and Offline - Gentzkow, Matthew (American Economic Review, 2014)
Popular accounts suggest that advertising revenue per unit of consumer attention is lower online than offline, and has fallen in traditional media as the Internet has made advertising markets more competitive. I assess these claims theoretically and empirically, and compare the patterns we observe for the Internet to trends in advertising around the introduction of television and radio. The evidence suggests that the price of attention for similar consumers is actually higher online than offline, and that the growth of new media is not robustly associated with a declining price of attention.